The Challenges of Diagnosis and Management of SuspectedAutoimmune Hepatitis in a 34-Year-Old Woman with PeriodicParalysis and Graves’ Disease - Larasati, Yeni; Wahono, C. Singgih (Jurnal Penyakit Dalam Indonesia, 2021)
Periodic paralysis hypokalemia is a muscle weakness that can be caused by hyperthyroidism due to Graves’ disease. The prevalence reaches 10% of patients with periodic paralysis hypokalemia with symptoms of thyrotoxicosis. Graves’ disease is an immune system disorder that can cause other organ dysfunction, such as autoimmune hepatitis. Currently, the diagnosis of autoimmune hepatitis is still a challenge for clinicians due to limited supporting examination facilities, such as SMA, AMA, anti-LKM-1. This article discusses a case of a 34-year-old woman with limb weakness for 3 months, losing 4 kg of weight in 1 month, often feeling hungry, restless, having trouble sleeping, unable to stand the heat, and palpitation. Her urine was looked like a tea color for the last 10 days. Laboratory examination results showed an increase in alanine transaminase (ALT) levels 256 U/I and aspartate aminotransferase (AST) 142 U/I, accompanied by an increase in total bilirubin levels of 12.09 mg/dl, direct bilirubin 10.5 mg/ dl. Markers of hepatitis B (HbsAg) and anti-HCV were negative. The potassium level was 2.29 mmol/L and the antinuclear antibody test was 1.3 IU/ml. Thyroid-stimulating hormone (TSH) <0.01 uIU/ml, and FT4 5.46 mg/dl. Abdominal ultrasound showed chronic liver disease. Histopathology of liver tissue showed chronic hepatitis with inflammatory infiltration. The patient had been treated with thiamazole, potassium supplements, propranolol, and prednisone. As a result, the patient’s condition and liver enzyme tests improved